Consumer goods and services inflation in Latin America during the COVID-19 pandemic - VÍCTOR MANUEL CUEVAS AHUMADA; IGNACIO PERROTINI HERNÁNDEZ (Brazilian Journal of Political Economy)
ABSTRACT Consumer goods inflation significantly exceeded consumer services inflation in many nations during the COVID-19 pandemic. Therefore, this paper evaluates the key drivers of goods prices and services prices in eight Latin American countries during that period. To that end, we employ two fixed effects panel data models involving such nations and monthly data from January 2020 to December 2022. The models’ specification allows for assessing the impact of fiscal and monetary policies, exchange rate fluctuations, and two pandemic-related variables, on goods prices and services prices. The models are estimated through two-stage least squares complemented with other remedial measures.